Identificación de los factores internos que inciden en el desempeño competitivo de la Cooperativa de Ahorro y Crédito "Sierra Centro" de la ciudad de Latacunga. - Millingalli Ayala, Jenny Marlene (2018)
The purpose of this researching project was to identify the internal factors that affect the competitive performance of the Sierra Centro Savings and Credit Cooperative in Latacunga city, with the purpose of detecting the deficiencies that exist in aspects such as management of administration, human resource, managerial capacity, innovation and technology, finances, service capacity, growth and development which are important aspects to improve competitive performance. For which it was necessary to carry out the fieldwork, through the type of descriptive and documentary study, which allowed us to correctly describe the current situation of the aforementioned financial institution, with the quantitative research approach which allowed the numerical measurement and thus the statistical analysis could be carried out, finally the interview was applied to the manager and surveys to all the personnel working in the cooperative, and the respective analysis of results was carried out and the incidence of the internal factors of the competitive performance of the cooperative was determined. Cooperativa de Ahorro y Crédito Sierra Centro of Latacunga, by means of which it allowed to take decisions and with it the goals and objectives set and in turn can stay in the competitive market.